Solidification characteristic of Metal Matrix composite produced by sand casting - N., Fatchurrohman; S., Sulaiman; M. K. A., Ariffin; A. A., Faieza (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.